254 Driving Improvement for Testicular Cancer Patients within a Urology Unit at a District General Hospital. (19th August 2022) - Hayes, J; Nayak, A; Pullar, B; Vasdev, N
Abstract: Aim: Assess the proportion of patients undergoing: (1) Preoperative assessment of the testicle, including serum tumour markers (STM) and testicular ultrasound (US), (2) Orchidectomy within 3 weeks of US diagnosis, and (3) Radiological staging (CT) within 3 weeks of surgery. Method: Patients who had a radical inguinal orchidectomy for probable testicular malignancy were identified, between January and October 2021, via the electronic theatre system. Clinical data, including blood results, imaging, and histopathology, were obtained via the ICE reporting system. Results: 21 patients underwent orchidectomy during the 10-month period. The median age was 37 (26–89) with the majority (81%) presenting with a painless testicular lump. On final histopathology, 11 (52.3%) demonstrated classical seminoma and 6 (28.6%) a mixed germ cell tumour. Testicular US was performed on all patients prior to surgery and 95.2% had the full complement of STM taken. Unfortunately, the Lactate Dehydrogenase (LDH) in 65% of these patients had haemolysed. The mean time from US diagnosis to orchidectomy was 20.1 days (4–29), with 66.6% of patients operated on within 3 weeks. A staging CT was performed on 84.6% of patients within 3 weeks of surgery. Conclusions: Delays from testicular cancer diagnosis to surgery can impact on both disease stage and ultimately outcome. Following local presentation of our results, whilst liaising with biochemistry, various factors have been addressed to help mitigate the risk of STM sample haemolysis (including sample drawing, transport, and processing). In addition, a more formal pathway has since been instigated to ensure patients are undergoing orchidectomy in a timely fashion.